2017
DOI: 10.1007/s11060-017-2602-x
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary radiogenomics association between MR perfusion imaging parameters and genomic biomarkers, and their predictive performance of overall survival in patients with glioblastoma

Abstract: The radiogenomics association of neovascularization is important for overall survival (OS) in glioblastoma patients and remains unclear. The purpose of this study is to assess the association between MR perfusion imaging derived parameters and genomic biomarkers of glioblastoma, and to evaluate their prognostic value. This retrospective study enrolled 41 patients with newly diagnosed glioblastoma. The mean and maximal relative cerebral blood volume (rCBV) ratio (rCBV and rCBV), derived from MR perfusion weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Conventional and advanced magnetic resonance imaging have been widely used for gliomas grading and genotyping (8)(9)(10)(11). As previously reported, conventional magnetic resonance imaging (cMRI) features including tumor location might predict molecular profiles in GBMs in some instances (12,13).…”
Section: Introductionmentioning
confidence: 95%
“…Conventional and advanced magnetic resonance imaging have been widely used for gliomas grading and genotyping (8)(9)(10)(11). As previously reported, conventional magnetic resonance imaging (cMRI) features including tumor location might predict molecular profiles in GBMs in some instances (12,13).…”
Section: Introductionmentioning
confidence: 95%
“…Phosphatidylinositol 3 kinase (PI3K) / protein kinase B (AKT) / mammalian target of rapamycin (mTOR) signaling pathway plays an important role in the genesis and development of many kinds of tumors. The signaling pathways through PI3K and AKT gene mutation and ampli cation, oncogene receptor activation, gene expression reduction of phpsphase and tensin homologue deleted on chromosome 10 (PTEN), and regulation of vascular endothelial growth factor (VEGF) expression and other mechanisms to promote tumor cell growth and angiogenesis [3][4][5]. Studies have shown that PTEN is a tumor suppressor gene with dual speci c phosphatase activity, and its gene mutation and loss of expression can cause the P13K / AKT / mTOR signaling pathway to be activated, leading to abnormal cell proliferation, in ltration and metastasis [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the emergence of radiogenomics, combing radiomics image features and genomics, allows the study of GBM more comprehensively. For example, MRI parameters revealed that haemodynamic abnormalities were associated with the expression level of the mTOR-EGFR pathway in [10]. Based on previous findings, we aimed to investigate the machine learning based methods in combination with radiogenomics to study the associations among MRI features, genomics and the survival rates in GBM patients.…”
Section: Introductionmentioning
confidence: 99%